The Influence of Behavioral Finance on Investment Decisions: A Systematic Literature Review - Ferdian, Romi (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Behavioral finance is a discipline that combines psychology with economic theory to understand the influence of cognitive biases on investment decisions. This research aims to explore the role of cognitive biases, such as overconfidence, herding, and aversion to losses, in long-term and short-term investment decision making and their impact on retail and institutional investors. Using systematic methods with the PRISMA approach, this study analyzes relevant literature to identify patterns and differences in the impact of bias. The findings show that cognitive biases significantly influence investment decisions, with clear differences between long-term and short-term investments, as well as between retail and institutional investors. The implications of this research include the development of more rational investment strategies and the creation of effective policies to reduce the negative effects of cognitive bias.